Um jogo eletrônico como ferramenta complementar no ensino de PHP - Kisielewicz, Leandro Augusto (2012)
In several disciplines that involve computer programming, difficulties are found. On of them is to keep the students motivated by activities such as solving programming problems to memorize contents. Considering the educational electronic games as objects that attract the attention of the student, sought to link them to the classroom in order to test the hypothesis of this study, which is that games can promote an increase in motivation and thereby improving the students' interest and engagement in activities. To verify the hypothesis was developed an educational game, able to automatically evaluate the answers given by players. The game was implemented in a programming discipline. Through a qualitative analysis of responses from a questionnaire with open questions and observation of student performance, the study found that the combined use of the game with the method traditionally used in the discipline had a positive impact, increasing the quality of participation of students in programming tasks and exercises.